First photographic evidence of Fishing Cat Prionailurus viverrinus Bennett, 1833 and Clouded Leopard Neofelis nebulosa Griffith, 1821 (Carnivora: Felidae) in Parsa National Park, Nepal - Shashank Poudel (Journal of Threatened Taxa, 2019)
Twelve cat species were recorded in Nepal including the largest, Tiger Panthera tigris, and the smallest, Rusty-spotted Cat Prionailurus rubiginosus.  There is more research on the Panthera species than on small wild cats; consequently, the conservation status, distribution, and ecology of small cat species are poorly known.  In this article, we report on the first photographic evidence of Clouded Leopard Neofelis nebulosa and Fishing Cat Prionailurus viverrinus in Parsa National Park in southern central Nepal during a camera trap survey targeted at the tiger between 2014 and 2016.  There were only single detections of each species; this does not give enough information to establish distribution or conservation status of either of the species in Parsa National Park.  Further targeted surveys are needed to establish the significance of this protected area for the conservation of these two species.